Genome-wide identification and characterization of TCP genes involved in ovule development of Phalaenopsis equestris - Lin, Yu-Fu; Chen, You-Yi; Hsiao, Yu-Yun; Shen, Ching-Yu; Hsu, Jui-Ling; Yeh, Chuan-Ming; Mitsuda, Nobutaka; Ohme-Takagi, Masaru; Liu, Zhong-Jian; Tsai, Wen-Chieh (Journal of experimental botany, 2016)
TEOSINTE-BRANCHED/CYCLOIDEA/PCF (TCP) proteins are plant-specific transcription factors known to have a role in multiple aspects of plant growth and development at the cellular, organ and tissue levels. However, there has been no related study of TCPs in orchids. Here we identified 23 TCP genes from the genome sequence of Phalaenopsis equestris. Phylogenetic analysis distinguished two homology classes of PeTCP transcription factor families: classes I and II. Class II was further divided into two subclasses, CIN and CYC/TB1. Spatial and temporal expression analysis showed that PePCF10 was predominantly expressed in ovules at early developmental stages and PeCIN8 had high expression at late developmental stages in ovules, with overlapping expression at day 16 after pollination. Subcellular localization and protein–protein interaction analyses revealed that PePCF10 and PeCIN8 could form homodimers and localize in the nucleus. However, PePCF10 and PeCIN8 could not form heterodimers. In transgenic Arabidopsis thaliana plants (overexpression and SRDX, a super repression motif derived from the EAR-motif of the repression domain of tobacco ETHYLENE-RESPONSIVE ELEMENT-BINDING FACTOR 3 and SUPERMAN, dominantly repressed), the two genes helped regulate cell proliferation. Together, these results suggest that PePCF10 and PeCIN8 play important roles in orchid ovule development by modulating cell division.